The Effect of the POGIL Learning Model on High School Students’ Problem Solving Abilities in Thermodynamics - Wilujeng, Indrawati; Wibowo, Hari Anggit Cahyo; Haris, Abdul (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
This research aims to describe the effect of the POGIL learning model on high school students’ problem-solving abilities in thermodynamics. This type of research is a quasi experiment with a quantitative approach and a one-group pretest-posttest design research. There are two classes used, namely the experimental class and the replication class. Both were given the same treatment to demonstrate the effect consistency. The sampling technique used convenience sampling. The sample size used was 55 students. Data collection techniques included interviews, questionnaires, and tests. Data analysis techniques used statistical tests, including n-gain test, normality test, homogeneity test, and hypothesis test. The n-gain test results indicate that the average n-gain of both classes falls within the middle criteria. Furthermore, the hypothesis testing results using the paired t-test show that H1 is accepted (α <0,005). Both findings indicate that there is an effect of the POGIL learning model on the problem-solving abilities of high school students in thermodynamics. Meanwhile, the hypothesis testing using the independent t test shows that H1 is also accepted (α <0,005), meaning there is a difference (inconsistency) in the effects between the experimental and replication classes.